The life-course offending trajectories of football hooligans. (January 2015) - Piquero, Alex R; Jennings, Wesley G; Farrington, David P
Football hooliganism has long occupied the social, media, and political landscapes of fans around the world. In this study, we use data from the Cambridge Study in Delinquent Development, a longitudinal study of a large sample of males followed from childhood to late middle adulthood, to examine the relationship between involvement in football hooliganism and both conviction frequency and conviction trajectories. Results show that, although hooligans differ from non-hooligans on several childhood and teenage risk factors, and that they also incur many more convictions than their non-hooligan counterparts, these relationships do not hold after carefully matching hooligans and non-hooligans on key risk factors. Football hooliganism, for the most part, seems to be part of a constellation of antisocial behaviors that also includes criminal offending.